New Chinese input method available. - Li Rongxia (Beijing Review, 1999)
A new technology called Chinese stroke code, which allows the input of Chinese characters into computers, became available in Beijing in October 1999 after years of experimentation. The method, invented by Wang Songping, utilizes 10 numbers to encode the basic strokes of Chinese characters, which makes it possible to dispense with the English-language keyboard. The use of only the number keyboard makes Chinese keyed entry technology possible, and this can therefore be widely applied in such communications products as mobile phones, telephones, laptops, electronic note pads, palm-held computers, and video compact disk players.